Characterisation of phosphate coacervates for potential biomedical applications. (April 2014) - Pickup, David M; Newport, Robert J; Barney, Emma R; Kim, Ji-Yung; Valappil, Sabeel P; Knowles, Jonathan C
In this study, amorphous (Na2 O) x (CaO)0.50− x (P2 O5 )0.50 · y H2 O (where x  = ∼0.15 and y =  ∼3) samples were prepared by a coacervate method. Thermal analysis showed that two types of water molecules were present in the coacervate structures: one type loosely bound and the other part of the phosphate structure. Structural studies using Fourier transform infrared spectroscopy (FTIR) and X-ray total diffraction revealed the samples to have very similar structures to melt-quenched glasses of comparable composition. Furthermore, no significant structural differences were observed between samples prepared using calcium nitrate as the calcium source or those prepared from calcium chloride. A sample containing ∼1 mol% Ag2 O was prepared to test the hypothesis that calcium phosphate coacervate materials could be used as delivery agents for antibacterial ions. This sample exhibited significant antibacterial activity against the bacterium Psuedomonas aeruginosa . FTIR data revealed the silver-doped sample to be structurally akin to the analogous silver-free sample.